PENGARUH BEBAN KERJA DAN KOMPENSASI TERHADAP TURNOVER INTENTION KARYAWAN UD ANEKA PLASTIK CABANG KEROBOKAN SINGARAJA - Nugraheni, Desita Amalia; Heryanda , Komang Krisna (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2026)
This research examines how workload and compensation shape the likelihood of employees intending to leave their organization. The methodological approach applied in this study follows a causal quantitative framework. The research took place at UD Aneka Plastik, Kerobokan Singaraja Branch, Kerobokan Singaraja Branch, with workload, compensation, and turnover intention serving as the research objects. A total of 42 employees constituted all members of the population were included as research samples through saturated sampling technique. Workload (X1) and compensation (X2) acted as the independent variables, whereas turnover intention (Y) was designated as the dependent variable. Questionnaires were employed as the primary instrument for gathering data, which were then analyzed through multiple linear regression using SPSS version 26.0 for Windows. The study yielded three key findings: (1) workload and compensation together exert a meaningful and statistically proven impact on employees' turnover intention at UD Aneka Plastik, Kerobokan Singaraja Branch; (2) workload carries a direct effect on employees' turnover intention, meaning that higher workload leads to greater turnover intention; and (3) compensation brings an opposing effect on employees' turnover intention, meaning that higher compensation leads to lower turnover intention at UD Aneka Plastik, Kerobokan Singaraja Branch.